Predicting factors for positive vaginal surgical margin following radical hysterectomy for stage IB1 carcinoma of the cervix - Sethawat Sethasathien (2018)
Background: To examine the incidence of positive vaginal surgical margins and determine the predicting factors following radical hysterectomy for stage IB1 carcinoma of the cervix. Materials and Methods: The clinical and histological data of 656 FIGO stage IB1 cervical cancer patients who had radical hysterectomy with bilateral pelvic lymphadenectomy (RHPL) from January 2003 to December 2012 were retrospectively reviewed and were analyzed for their association with a positive vaginal surgical margin. A p-value of < 0.05 was considered significant. Results: Thirty-five patients (5.3%) had positive vaginal surgical margins following RHPL; 24 (3.7%) for intraepithelial lesions and 11 (1.7%) for carcinoma. On multivariate analysis, microscopic vaginal involvement by high-grade squamous intraepithelial lesion and/or carcinoma (adjusted odd ratio (OR) 186.8; 95% confidence interval (CI) 48.5-718.5) and squamous histology (OR 8.7; 95% CI 1.7-44.0), were significantly associated with positive vaginal surgical margin. Conclusions: Microscopic vaginal involvement by HSIL and/ or carcinoma are strong predictors for positive vaginal surgical margins for stage IB1 cervical cancer patients undergoing radical hysterectomy. Preoperative 'mapping' colposcopy or other strategies should be considered to ensure optimal vaginal resection.